Desaturation during the pandemic: Covid or cognitive bias? - Ritika Nangia; Chetna Arvind Sethi; Niharika Dhiman (Journal of Family Medicine and Primary Care, 2022)
The coronavirus pandemic has put an unprecedented strain on our health care system. An urgent need for timely and accurate diagnosis coupled with an inordinate caseload and myriad overlapping signs and symptoms with other differentials is leaving physicians fatigued. This often leads to the use of mental shortcuts – “heuristics” by the strained mind and the inadvertent use of intuitive thought processes rather than the more controlled analytical thinking to cope and speed up the decision-making process. Availability bias – making a recent or vivid patient diagnosis more readily accessible to the mind – and anchoring bias – relying too heavily on a single symptom for deducing diagnosis – are among the most prevalent cognitive biases. Therefore, it is not unexpected that any new cases of acute onset respiratory illness may be mis-diagnosed as coronavirus disease 2019 during the pandemic, significantly impacting the morbidity and mortality of true diagnosis. To reduce the risk of patient harm, it is therefore imperative that medical practitioners be aware of the existence and influence of cognitive bias in clinical decision making and maintain sight of a variety of differential diagnoses to ensure that no adverse condition is overlooked.